Educational Supervision and Teacher Development: Addressing the Challenges of Instructional Improvement in Schools - Desrianti, Desrianti; Asmendri, Asmendri (Universitas Pakuan, 2024)
This study aims to explore the challenges of educational supervision in schools and its implications for improving teacher professionalism and instructional quality. Educational supervision plays a crucial role in guiding teachers toward better performance through continuous coaching, evaluation, and professional development. Principals, as supervisors, are expected to act as consultants and facilitators who understand teachers’ needs and provide constructive feedback for improvement. Using a literature-based research approach, this study synthesizes theoretical and empirical findings from various sources related to school supervision, teacher motivation, and job satisfaction. The analysis indicates that effective supervision contributes to teacher creativity, motivation, and satisfaction, which in turn enhance the quality of learning outcomes. However, several obstacles persist, including limited opportunities for teachers to develop pedagogical skills, lack of supervision consistency, and inadequate resources for instructional support. Therefore, strengthening the capacity of school leaders as supervisors and fostering a culture of reflective supervision are essential to advancing teacher competence and educational quality.